The Environmental education and entrepreneurship-training based on dorokdok’s used cooking oil waste in Suci Village - Fauziah, Nenden; Senania, Astri; Apriani, Riza; Handayani, Niknik; Yanti, Novi; Naima, Shafira Salsa; Muharram, Rahma Mekar; Yuningsih, Isma Aulia; Sumiarti, Imas; Ramadani, Jasmine Aura (Indonesian Journal of Community Empowerment (IJCE), 2025)
Used cooking oil from dorokdok frying pans, which potential to damage the environment, can become a new business opportunity. This community service program aims to raise environmental-awareness while also motivating people to become entrepreneurs by utilizing used cooking oil waste turn to aromatherapy candles. The community service method was carried out through an educational stage on how to handle used cooking oil waste to prevent environmental damage, followed by training on making aromatherapy candles. The educational results have successfully increased the participants' knowledge by 72.82%. The training results demonstrated the participants' skills in the process of making aromatherapy candles. The overall level of participant satisfaction with the community service process reached 82%. The results of this community service will be followed up with efforts to establish a joint business starting with the production of aromatherapy candles. This effort is expected to improve the economic and the environmental of Suci Village.